Rule #1 : the simple strategy for successful investing in only 15 minutes a week! - Town, Phil. (New York : Crown Publishers, 2006)
Phil Town wasn't always a very wealthy man. In fact, he was living on $4000 a year when some well-timed advice launched him into an investing self-education that revealed what the true'rules' are and how to make them work in one's favor. Chief among them, of course, is: don't lose money. Other rules are: don't diversify; think like an owner, not an investor. Town also believes strongly in putting your faith in managers who've proven their financial mettle, and who really have faith in the businesses they're running. The most controversial of the book's assertions is that giant 401(k) type mutual funds will regress to the mean, and in the next twenty years, the mean could be very disappointing. Fortunately, Town's stockpicking techniques are meant to walk investing phobes through the do-it-yourself process, equipping them with the tools they need to make quantum leaps toward financial security.--From publisher description.
Includes index.
Keywords: Investments; Finance, Personal